Penentuan Alergenisitas Protein Gen RB pada Kentang Produk Rekayasa Genetika Berdasarkan Studi Bioinformatika - Eny Ida Riyanti; Edy Listanto; A. Dinar Ambarwati (Jurnal AgroBiogen, 2015)
Genetically modified products (GMP) of Katahdin potato event SP951 containing RB gene resistant to late blight diseasescaused by Phytophtora infestans has been developed in the USA. This Katahdin SP951 potato has been crossed with localvarieties Atlantic and Granola for its development in Indonesia. In the release process, the GMP potato should be tested forenvironmental and food safety. One of the food safety assessment needs to be done by determining allergenicity of RB proteinwhether it is potential as allergen. This research aims to translate the RB gene sequence into RB protein sequence andinvestigate the potential RB protein as an allergen through bioinformatic studies. This study was performed based on thealignment with available protein allergens from available database websites. The predicted RB protein obtained from 2,913amino acids RB gene was a 971 amino acids length protein with ATG as a start codon and TAA as a stop codon. Bioinformaticsstudies of RB protein were performed using www.allergenonline.com, consisted of three searches, i.e. full-length search byFASTA, 80 amino acids search by FASTA, and 8 amino acid exact matches. For full-length alignment search, there are threeallergen proteins similar with RB protein sequence with the percentage identity of <35%, while for alignment with 80 aminoacids and 8 amino acids did not show similarity with any allergen protein in the database. It can be concluded that RB proteindid not have any potential as an allergen, as according to Codex Alimentarius guidelines for full-length alignment search, onlyprotein with identity greater than >50% indicating possible cross reactivity with protein allergen.